Manufacturing method for D03 type Fe3Al particle powder
The Fe-Al alloy metal particles are synthesized and heat treated by the gas phase condensation method, and the problems of high processing difficulty and cost of D03 type Fe-Al alloy materials in the prior art are solved, and industrialized production and efficient processing of materials are realized.
Patent Information
- Application Number
- JP2021046667
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-19
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2041-03-19
AI Technical Summary
It is difficult to industrially manufacture Fe-Al alloy materials with a D03-type regular lattice structure, especially when preparing thin films or bulk materials required for micron-scale thermoelectric conversion elements and thermoelectric power generation equipment, there are problems of difficulty and high cost of material processing.
Fe-Al alloy metal particles were synthesized by gas phase condensation method, and the Fe-Al alloy metal particles were heat treated to have a D03-type regular lattice structure to produce Al phase particle powder. The method includes mixing the raw materials of Fe and Al in a specific proportion, heating to a molten state by high frequency induction, then rapidly condensed into particles by gas phase condensation, and then heat treatment at a temperature of 275-575°C to ensure the D03-type structure of the material.
The industrial production of D03 type Fe-Al alloy material can be easily processed into parts with specific shapes, solve the problems of difficult and cost of material processing in the prior art, and provide an efficient method for preparing thermoelectric materials.
Smart Images

Figure 0007649176000006 
Figure 0007649176000007 
Figure 0007649176000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a powder consisting of particles of an Fe3Al intermetallic compound having a D03 type ordered lattice structure. [Background technology]
[0002] Fe3Al intermetallic compounds with a D03-type ordered lattice structure are known to be substances that exhibit a large anomalous Nernst effect, and are considered promising materials for constructing heat flow sensors and thermoelectric power generation devices. Non-patent literature 1 reports examples of the preparation of D03-type Fe3Al crystals, including the preparation of thin films by the molecular beam epitaxy method (MBE) and the preparation of single crystals by the Czochralski method (rotational pulling method).
[0003] It is desirable for a thermoelectric conversion element for constructing a heat flow sensor to have a thickness on the order of microns. In addition, in the case of a thermoelectric conversion element for realizing a thermoelectric generation device, it is desirable for the thermoelectric conversion element to be a bulk body with a thickness of about several millimeters. Film-forming techniques such as molecular beam epitaxy and sputtering can be used to prepare thin film samples on the order of several hundred nanometers, but are not suitable as a means for industrially manufacturing elements of D03 type Fe3Al crystals in terms of film-forming time and cost. It is possible to obtain large-sized D03 type Fe3Al single crystals by the Czochralski method. However, Fe3Al single crystals are very hard. It is very difficult to cut out elements of a given size from Fe3Al single crystals, especially to obtain thin elements on the order of microns. It is also difficult to crush Fe3Al single crystals into powder. Therefore, the technology for obtaining bulk D03 type Fe3Al single crystals is also not suitable as a means for industrially manufacturing elements of heat flow sensors and thermoelectric generation devices.
[0004] On the other hand, Non-Patent Document 2 shows an experiment in which Fe-Al alloy nanoparticles were produced by melting an Fe-Al alloy ingot with a hydrogen plasma arc, vaporizing it in a chamber, and then recovering the solidified powder. According to the description in this document, Fe3Al nanoparticles with a D03 structure were obtained. However, since the X-ray diffraction pattern using Cu-Kα rays (Fig. 3) does not show any {200} peaks (around 2θ = 30.9°) specific to Fe3Al crystals with a D03 structure, the crystal structure of the Fe-Al alloy nanoparticles actually produced is different from the description in the document and is not considered to be a D03 type ordered lattice structure. It is presumed that particles mainly composed of an Fe-Al alloy phase with an irregular structure were produced. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Akito Sakai et al. Iron-based binary ferromagnets for transverse thermoelectric conversion. Nature 581 (2020) 53-57. [Non-Patent Document 2] Tong Liu et al. Preparation and characteristics of Fe3Al nanoparticles by hydrogen plasma-metal reaction. Solid State Communications 125 (2003) 391-394. Summary of the Invention [Problem to be solved by the invention]
[0006] Until now, Fe3Al intermetallic compounds with a D03 type ordered lattice structure have been obtained in the form of thin films or single crystals. However, as mentioned above, it is extremely difficult to industrially manufacture parts of a specified shape using these thin film or single crystal materials. The object of the present invention is to provide a D03 type Fe3Al crystal material that can be easily processed into parts of a specified shape. [Means for solving the problem]
[0007] The object of the present invention is to provide a method for producing Fe-Al alloy particles having a molar ratio of Fe:Al in the range of 80.0:20.0 to 70.0:30.0 by a gas atomization method in which a molten metal composed of Fe and Al is rapidly cooled and solidified by blowing a stream of inert gas onto the molten metal in a gas phase space of an inert gas atmosphere; a superlattice forming step of generating an Fe3Al phase having a D03 type superlattice structure by heating and holding the metal particles at 275 to 575°C; This is achieved by a method for producing a D03 type Fe3Al particle powder having the above-mentioned formula.
[0008] In the superlattice forming step, it is preferable to generate an Fe3Al phase having a D03 type superlattice structure, in which the intensity ratio I{111} / I{220} of the diffraction peak heights of the {111} plane and the {220} plane of the D03 type Fe3Al superlattice in the X-ray diffraction pattern is 0.005 or more. The heating and holding time at 275 to 575°C can be, for example, 5 to 300 minutes. It is more preferable to set the heating and holding temperature to 300 to 550°C.
[0009] The size of the D03 type Fe3Al particle powder can be adjusted, for example, so that the average particle size based on the major axis falls within the range of 1 to 500 μm. Effect of the Invention
[0010] According to the present invention, it is possible to obtain a powder composed of particles of D03 type Fe3Al crystals. By using this powder, it is possible to easily manufacture parts of a predetermined shape using the D03 type Fe3Al intermetallic compound. [Brief description of the drawings]
[0011] [Figure 1] X-ray diffraction patterns using Co-Kα radiation for the test powders of Examples 1, 5, and 6. [Diagram 2] SEM photograph of precursor particle A powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] As a result of research, the inventors have found that fine particles mainly composed of Fe3Al phase with a D03 type ordered lattice structure can be obtained by subjecting fine particles of Fe-Al alloy having the stoichiometric composition of Fe3Al produced by rapid solidification or a composition slightly deviated from that composition to a heat treatment in which the particles are heated to and held at a temperature of about 500°C. Here, we disclose a manufacturing method that combines the synthesis of Fe-Al alloy particles by a gas atomization method with heat treatment, which is particularly suitable for producing D03 type Fe3Al particle powder consisting of spherical particles.
[0013] [Metal particle synthesis process] Fe-Al alloy particles are synthesized by the gas atomization method. Metal raw materials consisting of Fe and Al are used as the raw material. For example, a mixture of Fe powder and Al powder, or a Fe-Al alloy powder of a predetermined composition is used. The raw metal is melted in a crucible, and the molten metal is extruded into the gas phase space from the nozzle. The gas in the gas phase space is an inert gas such as N2 or Ar. The molten metal flow from the nozzle into the gas phase space is sprayed with inert gas at high pressure. The molten metal particles are rapidly cooled and solidified in the gas phase, and Fe-Al alloy particles within a predetermined composition range that includes the stoichiometric composition of Fe3Al are synthesized. By using the gas atomization method, spherical particles with an average particle size of, for example, microns can be obtained.
[0014] The solid particles of Fe-Al alloy synthesized by the gas atomization method are not yet Fe3Al particles having a D03 type superlattice structure. Therefore, the particles immediately after synthesis can be said to be precursor particles for superlattice formation into a D03 structure in the "superlattice formation process" described below. According to the study by the inventors, when the molar ratio of Fe to Al in the precursor particles made of Fe-Al alloy is in the range of 80.0:20.0 to 70.0:30.0, a phase of Fe3Al intermetallic compound having a crystal structure of D03 type superlattice can be obtained. That is, the stoichiometric molar ratio of Fe to Al in Fe3Al is 75.0:25.0, but D03 type Fe3Al particles exhibiting a D03 type superlattice structure can be obtained in the above composition range around that. Here, the term "D03 type Fe3Al particles" as used in this specification refers to particles of an Fe-Al alloy having the stoichiometric composition of Fe3Al or a composition slightly deviated from that composition, and a powder consisting of these particles exhibits an X-ray diffraction pattern based on a regular lattice of the D03 type structure.
[0015] [Regular grid formation process] The precursor particles collected from the gas atomizer are subjected to a heat treatment to generate an Fe3Al phase having a D03 type ordered lattice structure, thereby obtaining "D03 type Fe3Al particles". In order to stably obtain D03 type Fe3Al particles, in the present invention, Fe-Al alloy particles (precursor particles) having a molar ratio of Fe to Al, Fe:Al, in the range of 80.0:20.0 to 70.0:30.0, are subjected to a heat treatment. The heat treatment can be performed by heating and holding the precursor particles at 275 to 575°C. The optimum holding time at that temperature can be found within a range of 5 to 300 minutes. In particular, it is more effective to set the holding temperature in the range of 300 to 550°C, and more effective to set the holding time in the range of 10 to 180 minutes. If the temperature is too low, if the heating holding time is too short, or if the temperature is too high, the ordering into the D03 structure is not sufficiently achieved. If the heating time is too long, there is a tendency for phase separation into the B2 structure (Fe-Al phase) and the bcc structure (α-Fe) to occur. The atmosphere during heating should be a non-oxidizing gas atmosphere or a vacuum. A vacuum atmosphere here means a state with a pressure of 1 Pa or less.
[0016] [X-ray diffraction peak height intensity ratio] Whether or not a powder of Fe-Al alloy is a "D03 type Fe3Al particle" can be determined by measuring the X-ray diffraction (XRD) pattern of the powder using Cu-Kα or Co-Kα radiation. In the D03 type Fe3Al crystal, the {111} peak of the D03 type crystal is observed at a diffraction angle 2θ position where the X-ray diffraction peaks of the B2 type FeAl intermetallic compound crystal or the bcc crystal of α-Fe are not observed. The {111} peak of the D03 type crystal appears near 2θ=26.7° when the X-ray source is Cu-Kα radiation, and near 2θ=31.1° when the X-ray source is Co-Kα radiation. On the other hand, the most intense X-ray diffraction peak of the D03 type Fe3Al crystal is the {220} peak, which appears near 2θ=44.2° when the X-ray source is Cu-Kα radiation, and near 2θ=51.9° when the X-ray source is Co-Kα radiation.
[0017] Here, Fe-Al alloy powders that exhibit an X-ray diffraction pattern in which the intensity ratio I{111} / I{220} of the diffraction peak heights of the {111} and {220} planes in the Fe3Al ordered lattice of the D03 type structure is 0.005 or more are judged to be D03 type Fe3Al particles. Fe-Al alloy powders with the above intensity ratio I{111} / I{220} of 0.005 or more can be evaluated as having a high level of order in the atomic arrangement as an ordered lattice. The calculated intensity ratio I{111} / I{220} of the Fe3Al ordered lattice of a complete D03 type structure is 0.067 when the X-ray source is Cu-Kα radiation and 0.07 when the X-ray source is Co-Kα radiation, and it is known to be roughly equivalent regardless of the X-ray source.
[0018] The highest intensity {220} peak of the D03 type Fe3Al crystal is close in diffraction angle 2θ to the highest intensity {110} peak of the B2 type FeAl crystal and the highest intensity {110} peak of the α-Fe crystal, so in an X-ray diffraction pattern in which these peaks appear simultaneously, the peaks overlap each other. In such a case, the peak intensity I{220} of the {220} plane of the D03 type Fe3Al crystal can be determined by using the height of one of the overlapping peaks.
[0019] In addition to the {111} peak, a {200} peak is also observed in the D03 type crystal. The {200} peak of the D03 type Fe3Al crystal appears near 2θ=30.9° when the X-ray source is Cu-Kα radiation, and near 2θ=36.0° when the X-ray source is Co-Kα radiation. However, the position of this {200} peak is close to the position of the {100} peak of the B2 type FeAl crystal. Therefore, the presence of the peaks near 2θ above alone cannot identify the D03 type Fe3Al crystal. In order to determine the formation of the D03 type Fe3Al crystal, it is extremely effective to focus on the presence of the above-mentioned {111} peak that appears at a 2θ position that does not overlap with the diffraction peaks from the B2 type FeAl crystal or the disordered phase. In addition, in the powder of the D03 type Fe3Al particles of the present invention, in addition to the above-mentioned intensity ratio I{111} / I{220} being 0.005 or more, it is more preferable that the intensity ratio I{200} / I{220} of the diffraction peak heights of the {200} plane and the {220} plane is also 0.005 or more.
[0020] Here, the peak intensity I{hkl} of the {hkl} plane in the X-ray diffraction pattern can be determined as follows. (How to determine the peak intensity I{hkl} of the {hkl} plane in an X-ray diffraction pattern) The X-ray diffraction pattern of the target powder is measured using Cu-Kα or Co-Kα radiation as the X-ray source. The peak intensity I{hkl} of the {hkl} plane is the maximum value I of the peak when measurement data in a specified range of 2θ including the background parts on both sides of the {hkl} peak is extracted and fitted by the least squares method using a pseudo-Voigt function f(2θ). The following formula can be used for the pseudo-Voigt function. In this case, the background is approximated as a straight line and expressed as A+B2θ. C is the normalization constant of the peak. n, m, and H are fitting parameters. The maximum value I of the peak is determined by the following formula (1).
number
[0021] The 2θ range for extracting data for determining I{hkl}, i.e., the above-mentioned "predetermined range including the background parts on both sides of the {hkl} peak", can be, for example, when using Co-Kα radiation as the X-ray source, the 2θ range for I{111} measurement can be 30 to 33°, the 2θ range for I{200} measurement can be 35 to 37°, and the 2θ range for I{220} measurement can be 50 to 55°. The following literature is useful for the analysis method of X-ray diffraction patterns by fitting using the pseudo-Voigt function. Reference: Hideho Toratani, "6. Profile Functions and Pattern Decomposition Methods", Journal of the Crystallographic Society of Japan 34, 86 (1992)
[0022] [Particle shape] It is more preferable that the D03 type Fe3Al particles are spherical. The spherical shape of the particles is advantageous in terms of, for example, improving the sintering density when forming a thermoelectric element, and improving the fluidity and filling rate when processing into a sintering paste. More specifically, it is desirable that the average circularity of the particles constituting the powder is 0.80 or more. According to the manufacturing technique described below, a powder composed of spherical D03 type Fe3Al particles can be obtained. The average circularity can be determined as follows.
[0023] (How to calculate average circularity) The powder to be measured is observed with a SEM (scanning electron microscope), and all particles whose outlines can be seen in the SEM image of a randomly selected field of view are regarded as the particles to be measured. The circularity of each particle to be measured is calculated using the following formula (2). Circularity = 4πS / L 2 …(2) where S is the area of the particle on the image (μm 2 ), L is the perimeter of the particle on the image (μm). The circularity measurement is performed on SEM images of one or more randomly selected fields of view so that the total number of particles to be measured is 50 or more, and the average circularity of the particles constituting the powder is determined by dividing the sum of the circularities of the individual particles by the total number of particles to be measured.
[0024] [Average particle size of powder] In the present invention, it is possible to obtain D03 type Fe3Al particle powder having a particle size on the order of microns. For example, the target particle is one whose average particle size based on the major axis determined from an SEM image is in the range of 1 to 500 μm. Depending on the particle synthesis device used, the major axis may be adjusted to a range of 1 to 300 μm, or to a range of 5 to 100 μm. Here, the "major axis" is the length of the major axis of an ellipse obtained by approximating the outline of a particle on an SEM image. However, if the ellipse is a perfect circle, it is the diameter of the circle. The average particle size can be determined as follows.
[0025] (How to determine the average particle size) The powder to be measured is observed with a SEM (scanning electron microscope), and all particles whose outlines can be grasped in the SEM image of a randomly selected field of view are regarded as the particles to be measured, and the major axis of each particle to be measured is measured on the image. This major axis measurement is performed on SEM images of one or more randomly selected fields of view so that the total number of particles to be measured is 500 or more. A histogram of the major axis r of the particles to be measured is calculated using the following formula:
number
number
[0026] The particle size distribution can also be adjusted by classification or by mixing two or more types of powders with different average particle sizes. EXAMPLES
[0027] [Example 1] (Synthesis of precursor particles by gas atomization method) As the Fe raw material, wire rod cut pieces (manufactured by JFE Steel Corporation, diameter 5.5 mm x length 10 mm, purity 99.9% or more) were prepared. As the Al raw material, shot-like particles (manufactured by Kojundo Chemical Laboratory, particle size 5-10 mm, purity 99.99% or more) were prepared. These Fe raw materials and Al raw materials were weighed and mixed so that the atomic ratio was Fe:Al = 75:25. This mixture was placed in a water-cooled copper crucible with a diameter of 80 mm and heated at 1500 °C for 15 minutes by high-frequency induction heating to produce a molten Fe3Al alloy. Using a nozzle made of boron nitride (inner diameter 2 mm), the above molten metal was extruded from the nozzle into the gas phase space, and metal particles were synthesized by the gas atomization method in which Ar gas was sprayed onto the extruded molten metal. The gas nozzle diameter was 40 mm, the gas spray pressure was 6 MPa, and the spray angle was 15°. The obtained metal particles were collected and classified using two types of sieves with openings of 90 μm and 20 μm to extract particles with a particle size of 20 to 90 μm. The extracted particles are called "precursor particles A." When the composition of precursor particles A was analyzed by EDX (energy dispersive X-ray analysis), the atomic ratio of Fe to Al in the powder of precursor particles A, Fe:Al, was 76.2:23.8. The EDX device used was a Bruker XFlash6130 attached to a SEM (scanning electron microscope) (the same applies to each of the following EDX analysis examples). Figure 2 shows an example of an SEM (scanning electron microscope) photograph of the powder of precursor particle A. SEM observation was performed using a JEOL JSM-7800F (the same applies to each of the following examples). The length of the white scale bar shown near the bottom center of the photograph corresponds to 10 μm.
[0028] (Average particle size of precursor particles) According to the "How to calculate the average particle size" above, the average particle size was calculated from the images taken by SEM observation. The software used was "Origin 2020." The bin width was set to 30 nm, and the log-normal distribution function f(r) was fitted by the Levenberg-Marquardt method to determine the fitting parameters θ and μ. The average particle size was calculated based on these θ and μ. As a result, the average particle size of precursor particle A was determined to be 54.7 μm. (Average circularity of precursor particles) The average circularity of the precursor particles A was calculated according to the above-mentioned "Method of calculating the average circularity" and found to be 0.785. 2 was 0.136.
[0029] (Heat treatment) The powder of precursor particle A was subjected to a heat treatment in a tubular furnace under a N2 atmosphere while flowing N2 gas at 20 L / min at a holding temperature of 300°C for a holding time of 180 minutes. The heat-treated powder was used as a test powder for the following experiments.
[0030] (X-ray diffraction intensity ratio of test powder) The X-ray diffraction pattern of the test powder was measured using an X-ray diffractometer (Malvern Panalytical, Empyrean) under the conditions of Co-Kα radiation, tube voltage 45 kV, and tube current 45 mA. Since the peaks due to Kα1 and Kα2 were superimposed on the obtained X-ray pattern, the peaks due to Kα2 were removed using the Rachinger method to obtain an X-ray diffraction pattern consisting only of peaks due to Kα1. At this time, the intensity ratio of Kα1 to Kα2 was set to Kα1 / Kα2=0.5, and calculations were performed using X-ray diffraction analysis software (Malvern Panalytical, HighScore Plus). For this X-ray diffraction pattern consisting only of peaks derived from Kα1, the heights of the diffraction peaks of the {111} and {220} planes of the D03 type Fe3Al crystal were determined using a graph analysis software (Origin, manufactured by OriginLab Corporation) according to the above-mentioned "How to determine the peak intensity I{hkl} of the {hkl} plane in an X-ray diffraction pattern", and the intensity ratio I{111} / I{220} of the diffraction peak heights of the {111} and {220} planes was calculated. Here, the 2θ range for the I{111} measurement was 30 to 33°, and the 2θ range for the I{220} measurement was 50 to 55°.
[0031] The X-ray diffraction pattern of the powder sample in this example is shown in Figure 1. The intensity ratio of the diffraction peak heights I{111} / I{220} in this example was 0.005, confirming that the D03 type Fe3Al particles were obtained by the above heat treatment.
[0032] (Composition of test powder) When measured by EDX (energy dispersive X-ray analysis), the atomic ratio of Fe to Al in the powder sample of this example was Fe:Al=76.3:23.7.
[0033] (Average particle size of test powder) According to the above-mentioned "Method of determining average particle size", the average particle size was determined in the same manner as in the case of the precursor powder, and the average circularity after the above heat treatment was found to be 53.5 μm. (Average circularity of test powder) The average circularity was calculated according to the above-mentioned "Method of calculating the average circularity", and the average circularity after the heat treatment was 0.840. 2 was 0.129.
[0034] Tables 3 and 4 summarize the main experimental conditions and results for each example.
[0035] [Example 2] The same experiment as in Example 1 was carried out, except that the powder of precursor particles A was subjected to a heat treatment at a holding temperature of 350°C. In this example, the X-ray diffraction intensity ratio I{111} / I{220} was 0.005, and it was confirmed that D03 type Fe3Al particles were obtained by the above heat treatment.
[0036] [Example 3] The same experiment as in Example 1 was carried out, except that the powder of precursor particles A was subjected to a heat treatment at a holding temperature of 400°C. In this example, the X-ray diffraction intensity ratio I{111} / I{220} was 0.008, and it was confirmed that D03 type Fe3Al particles were obtained by the above heat treatment.
[0037] [Example 4] The same experiment as in Example 1 was carried out, except that the powder of precursor particles A was subjected to a heat treatment at a holding temperature of 450°C. In this example, the X-ray diffraction intensity ratio I{111} / I{220} was 0.012, and it was confirmed that D03 type Fe3Al particles were obtained by the above heat treatment.
[0038] [Example 5] The same experiment as in Example 1 was carried out, except that the conditions for the heat treatment applied to the powder of precursor particles A were a holding temperature of 450° C. and a holding time of 10 minutes. The X-ray diffraction pattern of the powder sample in this example is shown in Figure 1. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.010, confirming that D03 type Fe3Al particles were obtained by the above heat treatment.
[0039] [Example 6] The same experiment as in Example 1 was carried out, except that the powder of precursor particles A was subjected to a heat treatment at a holding temperature of 500°C. The X-ray diffraction pattern of the powder sample in this example is shown in Figure 1. The X-ray diffraction intensity ratio I{111} / I{220} in this example was 0.020, confirming that D03 type Fe3Al particles were obtained by the above heat treatment.
[0040] The magnetic properties of the powder sample in this example were measured using a VSM (Quantum Design, DynaCool). The measurement conditions were a maximum applied magnetic field of 2 T, a sweep speed of 0.01 T / sec, a time constant of 1 sec, an amplitude of 2 mm, and a frequency of 40 kHz. The measurement results showed that the saturation magnetization was 144 A·m at a temperature of 300 K. 2 / kg, residual magnetization is 5.3 A m 2 / kg, coercive force is 7.4kA m 2 / kg (93 Oe).
[0041] [Example 7] The same experiment as in Example 1 was carried out, except that the powder of precursor particles A was subjected to a heat treatment at a holding temperature of 550°C. In this example, the X-ray diffraction intensity ratio I{111} / I{220} was 0.006, and it was confirmed that D03 type Fe3Al particles were obtained by the above heat treatment.
[0042] [Comparative Example 1] In this example, the above-mentioned powder of precursor particles A (not subjected to heat treatment) was used as a test powder, and the same measurements as in Example 1 were carried out. The X-ray diffraction pattern of the powder sample in this example did not show the {111} peak of the D03 type Fe3Al crystal. In other words, when the particles produced by the gas atomization method were not subjected to heat treatment, the D03 type superlattice structure was not obtained.
[0043] [Comparative Example 2] The same experiment as in Example 1 was carried out, except that the powder of precursor particles A was subjected to a heat treatment at a holding temperature of 250°C. The X-ray diffraction intensity ratio I{111} / I{220} in the X-ray diffraction pattern of the powder sample in this example was 0.003, and when the heat treatment temperature was as low as 250°C, D03 type Fe3Al particles were not obtained sufficiently.
[0044] [Comparative Example 3] The same experiment as in Example 1 was carried out, except that the powder of precursor particles A was subjected to a heat treatment at a holding temperature of 650°C. The X-ray diffraction pattern of the powder sample in this example did not show the {111} peak of the D03 type Fe3Al crystals, i.e., when the heat treatment temperature was as high as 650°C, D03 type Fe3Al particles were not obtained.
[0045] [Table 1]
[0046] [Table 2]
Claims
1. a metal particle synthesis step of synthesizing metal particles of an Fe-Al alloy having a composition in which the molar ratio of Fe:Al is in the range of 80.0:20.0 to 70.0:30.0 by a gas atomization method in which a molten metal composed of Fe and Al is rapidly cooled and solidified by blowing a stream of inert gas onto the molten metal in a gas phase space of an inert gas atmosphere; By heating and holding the metal particles at 275 to 575°C, it is possible to obtain Fe3Al having a D03 type ordered lattice structure, in which the intensity ratio I{111} / I{220} of the diffraction peak heights of the {111} plane and the {220} plane of the D03 type Fe3Al ordered lattice in an X-ray diffraction pattern is 0.005 or more. 3 A superlattice forming step for generating an Al phase; D03 type Fe 3 A method for producing Al particle powder.
2. The D03 type Fe according to claim 1, wherein the heating and holding temperature is 300 to 550° C. in the ordering step. 3 A method for producing Al particle powder.
3. The D03 type Fe according to claim 1 or 2, wherein in the ordering step, a particle powder having an average particle diameter of 1 to 500 μm based on the major axis is obtained. 3 A method for producing Al particle powder.